A flaky core-shell structure electromagnetic absorber and its preparation method and application

By adopting an electromagnetic absorber with a sheet-like core-shell structure, using the combination of sheet-like soft magnetic material and metal oxide-carbon composite shell, combined with the carbon nanotube cladding layer, the problems of traditional absorber density and narrow absorption bandwidth are solved, and the efficient and low-density electromagnetic wave absorption effect is achieved, widening the application scenarios and reducing costs.

CN118905215BActive Publication Date: 2025-03-25ZHEJIANG YUANBANG MATERIAL TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411397694.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-03-25
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

Traditional wave absorbers face problems such as large density, narrow absorption bandwidth, and poor controllability. Only with a large filling rate and thicker thickness can ideal wave absorbing effect be achieved, which limits its application areas.

Method used

An electromagnetic absorber with a sheet-like core-shell structure includes a sheet-like soft magnetic material as the core and a metal oxide-carbon composite shell as the shell, and a carbon nanotube cladding layer is provided on the shell surface. By controlling the thickness and width-thickness ratio of the sheet-shaped soft magnetic material, as well as the thickness and metal element content of the metal oxide-carbon composite shell layer, an absorbent with multi-interface characteristics and high magnetic permeability is formed.

Benefits of technology

It significantly improves the dielectric loss characteristics of the absorbent, reduces the conductivity, improves the impedance matching characteristics, enhances the electromagnetic absorption performance, and realizes the strong absorption characteristics of wideband electromagnetic waves in low density, reducing the amount of absorbing materials and manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118905215B_ABST
    Figure CN118905215B_ABST
Patent Text Reader

Abstract

The present invention specifically discloses an electromagnetic absorber with a flaky core-shell structure and a preparation method and application thereof. The electromagnetic absorber with a flaky core-shell structure comprises the following raw materials in parts by weight: a core and a shell covering the core; the core comprises a flaky soft magnetic material, and the shell is a metal oxide-carbon composite shell; the thickness of the flaky soft magnetic material is 1-1.5 μm, and the width-to-thickness ratio of the flaky soft magnetic material is 60-100; the thickness of the metal oxide-carbon composite shell is 200-300 nm, and the mass proportion of the metal oxide in the metal oxide-carbon composite shell is 30%-50%; the metal elements in the metal oxide-carbon composite shell include transition magnetic metal elements. The absorber of the present invention has the advantages of absorption bandwidth, good controllability and low density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of absorbing materials, and in particular to an electromagnetic absorber with a flaky core-shell structure and a preparation method and application thereof. Background Art

[0002] Electromagnetic absorbers can absorb and dissipate electromagnetic waves incident on materials, converting electromagnetic energy into other forms of energy such as heat energy, so as to effectively avoid electromagnetic wave scattering. However, traditional absorbers face a series of problems such as high density, narrow absorption bandwidth, and poor controllability. In addition, they can only achieve ideal absorbing effects at a high filling rate and thick thickness, which limits their application areas to a certain extent. Summary of the invention

[0003] In order to solve the problems in the prior art, the present invention provides an electromagnetic absorber with a sheet-like core-shell structure and a preparation method and application thereof.

[0004] In a first aspect, the present invention provides an electromagnetic absorber with a core-shell structure, which adopts the following technical solution:

[0005] An electromagnetic absorbent with a flaky core-shell structure, comprising an inner core and an outer shell covering the inner core; the inner core comprises a flaky soft magnetic material, and the outer shell is a metal oxide-carbon composite shell layer;

[0006] The thickness of the flaky soft magnetic material is 1-1.5 μm, and the width-to-thickness ratio of the flaky soft magnetic material is 60-100;

[0007] The thickness of the metal oxide-carbon composite shell layer is 200-300nm, and the mass proportion of the metal oxide in the metal oxide-carbon composite shell layer is 30%-50%; the metal elements in the metal oxide-carbon composite shell layer include transition magnetic metal elements.

[0008] The present invention uses a flaky soft magnetic material with a flaky structure as a core, and a metal oxide-carbon composite layer shell containing a transition magnetic metal element as a shell covering the core, and in the metal oxide-carbon composite shell, the metal oxide can be embedded in the carbon material, thereby forming an electromagnetic absorber with a core-shell structure and multi-interface characteristics, which can effectively improve the dielectric loss characteristics of the absorber, effectively reduce the electrical conductivity, and improve the impedance matching characteristics; further, the flaky core-shell structure electromagnetic absorber of the present invention has a larger shape anisotropy, a higher saturation magnetization intensity and a higher impedance matching characteristic than absorbers with other structures. The higher magnetic permeability in the high frequency range can further improve the magnetic permeability and magnetic flux of the flaky soft magnetic material by further controlling the thickness and width-to-thickness ratio of the flaky soft magnetic powder, which helps to further enhance the performance of the electromagnetic absorber; finally, the flaky core-shell structured electromagnetic absorber of the present invention can be spread out in the matrix forming the absorbing material, and it is easier to form a surface contact effect, so that the contact area between the electromagnetic absorbers is significantly increased, and the particles are more easily overlapped to form a conductive network structure, which significantly improves the dielectric loss, thereby greatly reducing its usage in the absorbing material and reducing the manufacturing cost of the absorbing material.

[0009] Preferably, a coating layer is provided on the surface of the shell, and the coating layer comprises carbon nanotubes.

[0010] The present invention further arranges carbon nanotubes as a coating layer on the surface of the shell. On the one hand, the carbon nanotubes have a high specific surface area and excellent electron transmission performance, can effectively absorb and attenuate the incident electromagnetic waves, convert them into heat energy or other forms of energy and consume them, improve the electromagnetic loss characteristics of the absorbent, thereby helping to reduce the amount of absorbent-carrying absorbing materials and reduce the manufacturing cost of the absorbing materials; on the other hand, the light weight of the carbon nanotubes helps to reduce the density of the absorbent (the density of the absorbent prepared by the present invention is 1-1.2g / cm 3 ), which helps to broaden the application scenarios of absorbing materials. Therefore, the inclusion of carbon nanotubes in the coating layer can enable the absorber to achieve strong absorption characteristics of broadband electromagnetic waves at low density.

[0011] Preferably, the flaky soft magnetic material includes at least one of flaky carbonyl iron powder, flaky FeNi alloy and flaky FeCo alloy.

[0012] Preferably, the flaky soft magnetic material is prepared by a method comprising the following steps:

[0013] Spherical soft magnetic material is used as raw material, mixed with solvent and then prepared into flaky FeSiAl by ball milling; the ball-to-material ratio in the ball milling process is 20-25:1, the rotation speed is 360-400r / min, and the grinding time is 12-24h; the solvent includes alcohol, and the mass ratio of the alcohol to the spherical soft magnetic material is 1-1.5:1.

[0014] The raw material is ball-milled in a vibration ball mill for 15 hours to obtain the flaky soft magnetic material.

[0015] Preferably, the transition magnetic metal includes at least one of Mn, Fe, Co, Ni, Cu and Zn.

[0016] In a second aspect, the present invention provides a method for preparing an electromagnetic absorbent having a core-shell structure, using the following technical solution:

[0017] A method for preparing an electromagnetic absorber with a flaky core-shell structure comprises the following steps:

[0018] S1, mixing the carbon-nitrogen organic material, the transition magnetic metal source and the flaky soft magnetic material with water, ultrasonically stirring, and then continuing to stir to obtain a dispersion;

[0019] S2, mixing the dispersion with a buffer solution, stirring, performing solid-liquid separation, and vacuum drying the obtained solid product to obtain an intermediate product;

[0020] S3, mixing the intermediate product with a carbon source and performing heat treatment to obtain the electromagnetic absorbent.

[0021] Preferably, the buffer comprises a Tris-HCl buffer solution with a concentration of 0.8-1.2 mol / L.

[0022] Preferably, the carbon-nitrogen organic material includes at least one of dopamine and melamine;

[0023] The transition magnetic metal source includes at least one of a metal salt containing the transition magnetic metal and a metal organic framework containing the transition magnetic metal.

[0024] Preferably, in the dispersion, the mass ratio of the carbon-nitrogen organic material, the transition magnetic metal source, the flaky soft magnetic material, and the water is 1-3:1.5-2.5:3.5-5:480-500.

[0025] Preferably, the carbon source includes at least one of dicyandiamide, melamine and tannic acid.

[0026] By selecting the above-mentioned carbon source, after the carbon source is mixed with the intermediate product and subjected to heat treatment, a large number of staggered needle-shaped and rod-shaped carbon nanotubes can be formed on the surface of the intermediate product. These carbon nanotubes are clustered together, which is equivalent to forming a coating layer on the surface of the intermediate product.

[0027] Preferably, the mass ratio of the intermediate product to the carbon source is 0.8-1.2:1.

[0028] By controlling the mass ratio of the intermediate product to the carbon source, a sufficient number of coating layers can be formed on the outer shell surface of the electromagnetic absorber with a core-shell structure, which helps to cooperate with the core-shell structure to maximize the electromagnetic absorbing performance of the absorber and avoid the negative impact on the electromagnetic matching of the absorber due to excessive thickness of the coating layer (too many carbon nanotubes).

[0029] Preferably, the ultrasonic and stirring process in S1 lasts for 50-70 minutes, and the stirring time is continued for 1.5-3 hours; the stirring time in S2 is 22-26 hours; the heat treatment temperature in S3 is 700-900° C., and the heat treatment time is 2-4 hours.

[0030] By controlling the process parameters in each step, it is helpful for the raw materials to fully react with each other. Moreover, at the heat treatment temperature of the present invention, it is helpful for the carbon source to generate a sufficient number of carbon nanotubes to cooperate with the core-shell structure absorber, thereby significantly improving the wave absorption performance of the electromagnetic absorber with a core-shell structure of the present invention.

[0031] In a third aspect, the present invention provides an application of a sheet-like core-shell structured electromagnetic absorber in the field of wave absorption, using the following technical solution:

[0032] The invention discloses an electromagnetic absorber with a sheet-like core-shell structure and its application in the field of wave absorption. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 SEM image of flaky soft magnetic powder used as electromagnetic absorber.

[0034] Figure 2 This is the SEM image of the electromagnetic absorber of Example 2.

[0035] Figure 3 This is a partially enlarged view of the SEM image of the electromagnetic absorber of Example 2.

[0036] Figure 4 This is the XRD diagram of the electromagnetic absorber of Example 2.

[0037] Figure 5 This is the reflection loss spectrum of the electromagnetic absorber in Example 2.

[0038] Figure 6 This is the reflection loss spectrum of the electromagnetic absorber in Example 3. DETAILED DESCRIPTION

[0039] For better understanding and implementation, the technical solution of the present invention will be clearly and completely described below in conjunction with embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.

[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0041] Unless otherwise indicated, all numerical values ​​expressing quantities of ingredients, reaction conditions, and so forth used in the specification and claims are to be understood as modified by the term “about.” Accordingly, unless indicated to the contrary, the numerical parameters set forth herein are approximations that can vary depending upon the desired properties desired to be obtained.

[0042] As used herein, "and / or" means one or all of the mentioned elements.

[0043] As used herein, “including” and “comprising” encompasses the case where only the stated elements are present as well as the case where there are other elements other than the stated elements.

[0044] All percentages in the present invention are by weight, unless otherwise specified.

[0045] Unless otherwise indicated, "a", "an", "an" and "the" used in this specification are intended to include "at least one" or "one or more". For example, "a component" means one or more components, so more than one component may be considered and may be employed or used in the implementation of the embodiment.

[0046] Example 1

[0047] 1. Preparation of flaky soft magnetic materials

[0048] Spherical FeSiAl was used as a raw material, mixed with alcohol (the mass ratio of alcohol to the spherical FeSiAl was 1:1), and ball-milled on a planetary ball mill. The ball-to-material ratio during the ball milling process was 20:1, the rotation speed was 360 r / min, and the grinding time was 18 h to obtain flaky FeSiAl.

[0049] 2. An electromagnetic absorber with a flaky core-shell structure, comprising an inner core (a flaky FeSiAl alloy with a thickness of 1.2-1.4 μm and an aspect ratio of 70-90) and a metal oxide-carbon composite shell layer covering the inner core (wherein the mass proportion of the metal oxide is 40% and the transition magnetic metal element is Mn);

[0050] A method for preparing an electromagnetic absorber with a flaky core-shell structure comprises the following steps:

[0051] S1, mixing the carbon-nitrogen organic material (dopamine), the transition magnetic metal source (manganese chloride tetrahydrate) and the above-mentioned flaky soft magnetic material with deionized water in a mass ratio of 2:1.9:4:490, ultrasonically stirring for 60 minutes, and then continuing to stir for 2 hours to obtain a dispersion;

[0052] S2, mixing the above dispersion with 10 mL of 1 mol / L Tris-HCl buffer solution, stirring for 24 hours and then filtering, washing the obtained solid product with deionized water and then vacuum drying to obtain an electromagnetic absorber.

[0053] S3, heat treating the intermediate product at 800° C. for 3 h to obtain an electromagnetic absorber.

[0054] 3. Preparation of Absorbing Materials

[0055] The silica gel and the curing agent in a mass ratio of 100:1 were uniformly stirred in a beaker, and then the electromagnetic absorber was immersed in the mixture under vacuum assistance. Subsequently, the fully filled sample was cured in an oven at 60° C. for 4 hours to obtain an absorbing material.

[0056] Example 2

[0057] 1. Preparation of flaky soft magnetic materials

[0058] Spherical FeSiAl is used as a raw material, mixed with alcohol (the mass ratio of alcohol to the spherical FeSiAl is 1-1.5:1), and ball milled on a planetary ball mill. The ball-to-material ratio during the ball milling process is 20:1, the rotation speed is 360 r / min, and the grinding time is 18 hours to obtain flaky FeSiAl.

[0059] The SEM image of the flaky soft magnetic material (flaky FeSiAl alloy) used in preparing the electromagnetic absorber in this embodiment is as follows: Figure 1 shown.

[0060] 2. An electromagnetic absorber with a flaky core-shell structure, comprising an inner core (flaky FeSiAl with a thickness of 1.2-1.4 μm and an aspect ratio of 70-90) and a metal oxide-carbon composite shell layer covering the inner core (wherein the mass proportion of the metal oxide is 40% and the transition magnetic metal element is Mn);

[0061] A method for preparing an electromagnetic absorber with a flaky core-shell structure comprises the following steps:

[0062] S1, mixing the carbon-nitrogen organic material (dopamine), the transition magnetic metal source (manganese chloride tetrahydrate) and the above-mentioned flaky soft magnetic material with deionized water in a mass ratio of 2:1.9:4:490, ultrasonically stirring for 60 minutes, and then continuing to stir for 2 hours to obtain a dispersion;

[0063] S2, mixing the above dispersion with 10 mL of 1 mol / L Tris-HCl buffer solution, stirring for 24 hours and then filtering, washing the obtained solid product with deionized water and vacuum drying to obtain an intermediate product;

[0064] S3, mixing the above intermediate product with a carbon source (dicyandiamide) in a mass ratio of 1:1, and heat treating the mixture at 800° C. for 3 h to obtain an electromagnetic absorber.

[0065] The SEM image of the electromagnetic absorber prepared in this example is as follows: Figure 2 and Figure 3 The XRD test diagram of the electromagnetic absorber prepared in this embodiment is shown as Figure 4 As shown; the reflection loss spectrum of the electromagnetic absorber prepared in this embodiment is as shown Figure 5 shown.

[0066] 3. Preparation of Absorbing Materials

[0067] The silica gel and the curing agent in a mass ratio of 100:1 were uniformly stirred in a beaker, and then the electromagnetic absorber was immersed in the mixture under vacuum assistance. Subsequently, the fully filled sample was cured in an oven at 60° C. for 4 hours to obtain an absorbing material.

[0068] Example 3

[0069] 1. Preparation of flaky soft magnetic materials

[0070] Spherical FeSiAl is used as a raw material, mixed with alcohol (the mass ratio of alcohol to the spherical FeSiAl is 1-1.5:1), and ball milled on a planetary ball mill. The ball-to-material ratio during the ball milling process is 20:1, the rotation speed is 360r / min, and the grinding time is 18h to obtain flaky FeSiAl.

[0071] 2. An electromagnetic absorber with a flaky core-shell structure, comprising an inner core (flaky FeSiAl with a thickness of 1.2-1.4 μm and an aspect ratio of 70-90) and a metal oxide-carbon composite shell layer covering the inner core (wherein the mass proportion of the metal oxide is 40% and the transition magnetic metal element is Mn);

[0072] A method for preparing an electromagnetic absorber with a flaky core-shell structure comprises the following steps:

[0073] S1, mixing the carbon-nitrogen organic material (dopamine), the transition magnetic metal source (manganese chloride tetrahydrate) and the above-mentioned flaky soft magnetic material with deionized water in a mass ratio of 2:1.9:4:490, ultrasonically stirring for 60 minutes, and then continuing to stir for 2 hours to obtain a dispersion;

[0074] S2, mixing the above dispersion with 10 mL of 1 mol / L Tris-HCl buffer solution, stirring for 24 hours and then filtering, washing the obtained solid product with deionized water and vacuum drying to obtain an intermediate product;

[0075] S3, mixing the above intermediate product with a carbon source (dicyandiamide) in a mass ratio of 1:1, and heat treating the mixture at 900° C. for 3 h to obtain an electromagnetic absorber.

[0076] The reflection loss spectrum of the electromagnetic absorber prepared in this example is as follows: Figure 6 shown.

[0077] 3. Preparation of Absorbing Materials

[0078] The silica gel and the curing agent in a mass ratio of 100:1 were uniformly stirred in a beaker, and then the electromagnetic absorber was immersed in the mixture under vacuum assistance. Subsequently, the fully filled sample was cured in an oven at 60° C. for 4 hours to obtain an absorbing material.

[0079] Example 4

[0080] 1. Preparation of flaky soft magnetic materials

[0081] Spherical FeNi alloy is used as raw material, mixed with alcohol (the mass ratio of alcohol to the spherical FeNi alloy is 1.5:1), and ball milled on a planetary ball mill. The ball-to-material ratio during the ball milling process is 25:1, the rotation speed is 400 r / min, and the grinding time is 12 h to obtain flaky FeNi alloy.

[0082] 2. An electromagnetic absorber with a flaky core-shell structure, comprising an inner core (a flaky FeNi alloy with a thickness of 1-1.3 μm and an aspect ratio of 60-80) and a metal oxide-carbon composite shell layer covering the inner core (wherein the mass proportion of the metal oxide is 32% and the transition magnetic metal element is Fe);

[0083] A method for preparing an electromagnetic absorber with a flaky core-shell structure comprises the following steps:

[0084] S1, mixing the carbon-nitrogen organic material (melamine), the transition magnetic metal source (ferrous chloride tetrahydrate) and the above-mentioned flaky soft magnetic material with deionized water in a mass ratio of 1.2:1.5:3.6:480, ultrasonically stirring for 50 minutes, and then continuing to stir for 1.5 hours to obtain a dispersion;

[0085] S2, mixing the above dispersion with 10 mL of 0.8 mol / L Tris-HCl buffer solution, stirring for 22 h and then filtering, washing the obtained solid product with deionized water and vacuum drying to obtain an intermediate product;

[0086] S3, mixing the above intermediate product with a carbon source (dicyandiamide) in a mass ratio of 0.8:1, and heat treating the mixture at 800° C. for 2 h to obtain an electromagnetic absorber.

[0087] 3. Preparation of Absorbing Materials

[0088] The silica gel and the curing agent in a mass ratio of 100:1 were uniformly stirred in a beaker, and then the electromagnetic absorber was immersed in the mixture under vacuum assistance. Subsequently, the fully filled sample was cured in an oven at 60° C. for 4 hours to obtain an absorbing material.

[0089] Example 5

[0090] 1. Preparation of flaky soft magnetic materials

[0091] Spherical FeCo alloy is used as raw material, mixed with alcohol (the mass ratio of alcohol to the spherical FeCo alloy is 1.3:1), and ball milled on a planetary ball mill. The ball-to-material ratio during the ball milling process is 22:1, the rotation speed is 380r / min, and the grinding time is 24h to obtain flaky FeCo alloy.

[0092] 2. An electromagnetic absorber with a flaky core-shell structure, comprising an inner core (a flaky FeCo alloy with a thickness of 1.2-1.5 μm and an aspect ratio of 80-100) and a metal oxide-carbon composite shell layer covering the inner core (wherein the mass proportion of the metal oxide is 49% and the transition magnetic metal element is Ni);

[0093] A method for preparing an electromagnetic absorber with a flaky core-shell structure comprises the following steps:

[0094] S1, mixing the carbon-nitrogen organic material (melamine), the transition magnetic metal source (nickel-containing metal-organic framework) and the above-mentioned flaky soft magnetic material with deionized water in a mass ratio of 3:2.4:5:500, ultrasonically stirring for 70 minutes, and then continuing to stir for 3 hours to obtain a dispersion;

[0095] S2, mixing the above dispersion with 10 mL of 1.2 mol / L Tris-HCl buffer solution, stirring for 26 hours and then filtering, washing the obtained solid product with deionized water and vacuum drying to obtain an intermediate product;

[0096] S3, mixing the above intermediate product with a carbon source (tannic acid) in a mass ratio of 1.2:1, and heat treating the mixture at 800° C. for 4 h to obtain an electromagnetic absorber.

[0097] 3. Preparation of Absorbing Materials

[0098] The silica gel and the curing agent in a mass ratio of 100:1 were uniformly stirred in a beaker, and then the electromagnetic absorber was immersed in the mixture under vacuum assistance. Subsequently, the fully filled sample was cured in an oven at 60° C. for 4 hours to obtain an absorbing material.

[0099] Example 6

[0100] The difference between this embodiment and embodiment 2 is that the flaky soft magnetic powder is FeSiCr; the other steps, parameters and step settings are consistent with those of embodiment 2.

[0101] Comparative Example 1

[0102] The difference between this comparative example and Example 1 is that FeCo@C of equal weight is used to replace the electromagnetic absorber in the absorbing material in Example 1.

[0103] Comparative Example 2

[0104] The difference between this comparative example and Example 1 is that the inner core is spherical FeSiAl; the other steps and parameter settings are consistent with Example 1.

[0105] Comparative Example 3

[0106] The difference between this comparative example and Example 1 is that the width-to-thickness ratio of the flaky soft magnetic material is 30-50; the other steps and parameter settings are consistent with those of Example 1.

[0107] Comparative Example 4

[0108] The difference between this comparative example and Example 1 is that the mass proportion of the metal oxide in the metal oxide-carbon composite shell layer is 20%; the other steps and parameter settings are consistent with Example 1.

[0109] Comparative Example 5

[0110] The difference between this comparative example and Example 1 is that the mass proportion of the metal oxide in the metal oxide-carbon composite shell layer is 60%; the other steps and parameter settings are consistent with Example 1.

[0111] Comparative Example 6

[0112] The difference between this comparative example and Example 1 is that the thickness of the metal oxide-carbon composite shell layer is 20-30 nm; other steps and parameter settings are consistent with Example 1.

[0113] Comparative Example 7

[0114] The difference between this comparative example and Example 1 is that the thickness of the metal oxide-carbon composite shell layer is 500-800 nm; other steps and parameter settings are consistent with Example 1.

[0115] Test Method

[0116] 1. SEM morphology test

[0117] The morphology and microstructure of the aerogels prepared in the above examples and comparative examples were measured using a Sigma 300 scanning electron microscope (SEM) at an accelerating voltage of 5 kV.

[0118] 2. XRD test

[0119] The aerogels prepared in the above examples and comparative examples were tested using an Ultima IV X-ray diffractometer (XRD).

[0120] 3. Wave absorption performance test

[0121] The aerogels prepared in the above embodiments and comparative examples were immersed in molten paraffin, and vacuum was drawn to make them completely wetted. The aerogels were then taken out, and the paraffin was completely solidified. A coaxial ring sample with an outer diameter of 7.00 mm and an inner diameter of 3.04 mm was made into a mold, and then its electromagnetic parameters were tested with a vector network analyzer (model ZNA43, Rohde & Schwarz, Germany). According to the transmission line theory, the wave absorbing performance of the aerogel was obtained.

[0122] 4. Thickness and width-to-thickness ratio test of sheet soft magnetic materials

[0123] The thickness and width-to-thickness ratio of the aerogels prepared in the above examples and comparative examples were tested using a Sigma 300 scanning electron microscope (SEM) at an accelerating voltage of 5 kV.

[0124] Table 1

[0125]

[0126] Combined with Examples 1-5, Comparative Examples 1-7, Table 1 and Figures 1 to 6 It can be seen that the electromagnetic absorber of the present invention is prepared by using a flaky core-shell structure, and using a flaky soft magnetic material as the core and controlling the thickness and width-to-thickness ratio of the flaky soft magnetic material, using a metal oxide-carbon composite shell as the shell and controlling the content of the metal oxide in the metal oxide-carbon composite shell and the thickness of the shell, and coating a certain number of carbon nanotubes on the outer surface of the shell. The finally obtained absorber has multi-interface characteristics and high magnetic permeability, and has high saturation magnetization intensity, which can significantly improve the dielectric loss of the absorber; and the density of the absorber is small, and the added amount when used in the absorbing material accounts for a small proportion, which helps to reduce the application cost.

[0127] Combining Example 2, Example 6 and Table 1, it can be seen that the flake soft magnetic material in the present invention has good impedance matching characteristics when combined with other raw materials, and can significantly improve the absorbing performance of the absorber.

[0128] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.

Claims

1. An electromagnetic absorber with a core-shell structure, characterized in that: It comprises a core and a shell covering the core; the core comprises a flaky soft magnetic material, and the shell comprises a metal oxide-carbon composite shell layer; The thickness of the flaky soft magnetic material is 1-1.5 μm, and the width-to-thickness ratio of the flaky soft magnetic material is 60-100; The thickness of the metal oxide-carbon composite shell layer is 200-300 nm, and the mass proportion of the metal oxide in the metal oxide-carbon composite shell layer is 30%-50%; the metal elements in the metal oxide-carbon composite shell layer include transition magnetic metal elements; The surface of the shell is provided with a coating layer, and the coating layer includes carbon nanotubes; The electromagnetic absorber with a core-shell structure is prepared by a method comprising the following steps: S1, mixing the carbon-nitrogen organic material, the transition magnetic metal source and the flaky soft magnetic material with water, ultrasonically stirring, and then continuing to stir to obtain a dispersion; S2, mixing the dispersion with a buffer solution, stirring, performing solid-liquid separation, and vacuum drying the obtained solid product to obtain an intermediate product; S3, mixing the intermediate product with a carbon source and performing heat treatment to obtain the electromagnetic absorbent.

2. The electromagnetic absorber with a core-shell structure as claimed in claim 1, characterized in that: The flaky soft magnetic material comprises one of flaky carbonyl iron powder, flaky FeNi alloy and flaky FeCo alloy.

3. The electromagnetic absorber with a core-shell structure as claimed in claim 1, characterized in that: The transition magnetic metal includes one of Fe, Co and Ni.

4. The electromagnetic absorber with a core-shell structure as claimed in claim 1, characterized in that: The carbon-nitrogen organic material includes at least one of dopamine and melamine; The transition magnetic metal source includes at least one of a metal salt containing the transition magnetic metal and a metal organic framework containing the transition magnetic metal.

5. The electromagnetic absorber with a core-shell structure as claimed in claim 1, characterized in that: In the dispersion, the mass ratio of the carbon-nitrogen organic material, the transition magnetic metal source, the flaky soft magnetic material, and the water is 1-3:1.5-2.5:3.5-5:480-500.

6. The electromagnetic absorber with a core-shell structure as claimed in claim 1, characterized in that: The carbon source includes at least one of dicyandiamide, melamine and tannic acid.

7. The electromagnetic absorber with a core-shell structure as claimed in claim 6, characterized in that: The mass ratio of the intermediate product to the carbon source is 0.8-1.2:

1.

8. The electromagnetic absorber with a core-shell structure as claimed in claim 1, characterized in that: The ultrasonic and stirring process in S1 lasts for 50-70 minutes, and the stirring time is continued for 1.5-3 hours; the stirring time in S2 is 22-26 hours; the heat treatment temperature in S3 is 700-900°C, and the heat treatment time is 2-4 hours.

9. Use of the electromagnetic absorber with a core-shell structure as claimed in any one of claims 1 to 8 in the field of wave absorption.

Citation Information

Patent Citations

  • Carbon / magnetic electromagnetic wave absorbing material with sandwich structure and preparation method thereof

    CN113597252A

  • High-temperature-resistant dual-core-shell type electric-magnetic loss synergistic flaky carbonyl iron powder wave-absorbing agent and preparation method thereof

    CN117509744A

  • Electromagnetic wave absorbing material with high thermal conductivity

    CN117939865A